Effect of progestin-based hormonal contraceptives on genital inflammation and Th17 cell activation in adolescents at high risk for HIV infection - Konstantinus, Iyaloo (Department of Pathology, 2019)
Background: Adolescent girls and young women (AGYW) are at high risk for HIV infection, particularly in Southern Africa. In addition, some hormonal contraceptives (HC), such as progestin only-injectable contraceptives DMPA and NET-EN, have been associated with significantly increased risk for HIV infection. These HC together with sexual immaturity may increase activation of CD4+ T cells in the female reproductive tract (FRT), which are target cells for HIV infection. NuvaRing, also a long-acting progestin-containing contraceptive albeit topical, has recently been introduced to South Africa, and may offer an improved safety profile over NET-EN and DMPA in terms of HIV risk for young women. Recently, Th17 cells have been found to be disproportionally susceptible to HIV infection compared to the other T helper subsets although the impact of HC use on Th17 cell frequency and activation has not been investigated. Here, the impact of NuvaRing, NET-EN and combined oral contraceptive pills (COCPs) on the vaginal microenvironment of the FRT in AGYW was investigated as this relates to HIV risk, with particular focus on cervical Th17 cells and their related cytokines (Th17- related cytokines). Methods: One hundred and thirty HIV-negative adolescent girls between the age of 15 and 19 years were enrolled into a randomized, controlled crossover study comparing NuvaRing (n=45), NET-EN (n=45), and COCPs (n=40) for 16 weeks (~4 menstrual cycles). At crossover (16 weeks), the AGYW changed to another method for the following 16 weeks: 23 of those who used NuvaRing changed to NET-EN while 8 changed to COCPs; 23 of those who used NET-EN and 24 of those who used COCPs changed to NuvaRing. The protocol included three study visits in total (screening, crossover, study completion visits). Of the 130 adolescents enrolled, 107/130 reached the crossover visit and 92/130 reached the study exit visit. All adolescents were screened for STIs (multiplex PCR for Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis and Mycoplasma genitalium), BV (by Nugent scoring), and yeast (visible hyphae on gram stain) at all study visits. Data on relative abundance of vaginal microbial community types (CTs) from ectocervical swabs was available for this study, determined by 16S rRNA sequencing of the V4 region. Several genital samples were collected, including Digene cervical cytobrushes (for flow cytometry of cervical T cells) and menstrual cups at each study visit (for measurement of genital cytokine concentrations). Multiparameter flow cytometry was performed on cytobrushes to determine the frequency and activation status (CD38 and HLA-DR) of Th17 cells (defined by expression of CCR6+CCR10-), total CD3+CD4+ T cells and CD3+CD8+ including Tc17 cells (CD8+ CCR6+). A panel of fifteen Th17-related cytokines (IL-17A, IL-17F, IL-21, IL-22, IL-6, IL-1β, IL-23, IL-33, TNF-α, IL-4, IL-10, IL-25, IL-31, IFN-γ and sCD40L) were measured in genital secretions by Luminex. Results have been presented as an intention to treat (ITT) and per protocol (PP; which accounted for early switching of HC products prior to the crossover visit). Unless otherwise stated, all statistical testing was non-parametric, and P≤0.05 were considered significant. The BenjaminiHochberg method was used to adjust for multiple comparisons. Results: In the FRT of adolescents at baseline (before randomization), Th17 cells (CCR6+CCR10-) were found to be the major CD4+ T cell subset in cytobrushes (median 54.4%, IQR 43.7% - 64.3%) compared to CCR6-CCR10- (median 42.2%, IQR 33.5% - 52.6%), CCR6+CCR10+ (median 1.2%, IQR 0.4% - 2.8%) and CCR6-CCR10+ (median 0.8%, IQR 0.2% - 1.9%). Higher frequencies of Th17 cells expressed CCR5 compared to CCR6-CCR10- CD4+ T cells (median 68.0% vs 56.2% respectively, p< 0.0001). However, Th17 cell frequencies did not correlate with genital tract Th17-related cytokines at baseline. The presence of BV or STIs did not appear to influence either the frequencies or activation status of cervical Th17 cells. Although BV (Nugent 7-10) and having a nonLactobacillus-dominated vaginal microbiome (C1) was associated with increased concentrations of all Th17-related cytokines (IL-17A, IL-17F, IL-21, IL-22, IL-6, IL-1β, IL-23, IL-33, TNF-α, IL-4, IL-10, IL-25, IL-31, IFN-γ and sCD40L) compared to those without BV (Nugent 0-3) or C2/3, while adolescents with any STI had increased concentrations of IL-1β and IL-17A compared to those without an STI. After being randomized on to HC for 16 weeks, cervical cytobrush-derived immune cells were analysed within individuals in each arm (intra-individual) and between individuals in the three contraceptive arms, using both ITT and PP approaches. Although the frequency and activation status of cervical Th17 cells was similar across the three HC arms, adolescents using NuvaRing and NET-EN had significantly increased activation (CD38+HLA-DR+) on Th17 cells compared to their respective baselines (p=0.02 and p=0.03, respectively), which was not evident in those using COCPs. Furthermore, adolescents using NuvaRing had reduced frequencies of Th17 cells compared to baseline (p=0.001), which was not evident in those using NET-EN or COCPs. Although it was hypothesized that NuvaRing would offer some safety advantage over NET-EN in terms of mucosal HIV target cell activation, intra-individual analysis showed a significant increase in the frequency of highly activated cervical Th17 cells in those adolescents who started using the ring. A significant increase in genital tract concentrations of several Th17-related cytokine concentrations (including IL-21, IL-1β, IL-33, TNF-α, IL-4, IFN-γ and sCD40L) was noted in adolescents assigned to NuvaRing after 16 weeks of use, suggesting that the presence of the vaginal ring likely increased genital cytokine responses. Although the frequency and activation of CD8+ T cells was similar across HC arm, intra-individual analysis showed changes in the frequency of activation markers on CD8+ T cells in all HC arms. Moreover, frequencies of Tc17 cells were significantly reduced after 4 months of contraceptive use in each HC arm compared to baseline frequencies. Conclusion: In summary, CCR6+CCR10- Th17 cells were confirmed to be the major CD4+ T cell subset in the FRT of young adolescents. The use of NuvaRing led to decreased frequencies of Th17 cells which were highly activated, and was also associated with an increase in Th17-related cytokines compared to NET-EN and COCPs. All HC altered activation of cervical CD8+ T cells and reduced the frequencies of Tc17 cells. The dramatic alterations observed in cervical immune cells associated with the use of NuvaRing compared to NET-EN and COCPs warrant further investigations.